Identifying merit and potential beyond grades: opportunities and challenges in using contextual data in undergraduate admissions at nine highly selective English universities. (1st November 2020) - Mountford-Zimdars, Anna; Moore, Joanne
ABSTRACT: Highly selective higher education institutions (HEIs) are simultaneously mandated to enable access for populations which have traditionally been excluded ('equality'), and to ensure that admitted students have the potential to succeed in higher education ('excellence'). This article uses original empirical case study data from 2018, from nine highly selective English HEIs, to explore current uses of contextual data in undergraduate admissions. The results show that all participating HEIs thought holistically about their applicants. In particular, HEIs considered the context in which applicants had achieved their grades, and aimed to identify academic potential not captured by those grades. However, ideological and theoretical disagreements, as well as practical barriers, hamper a more widespread and consistent application of contextual data in English undergraduate admissions. The article therefore identifies further practical steps for HEIs and other stakeholders that would enable a more valid, evidence-based and coherent position on contextual data use across the HE sector. Overall, advancing more consistency in how contextual data are used might enable greater certainty among applicants, and those advising them, regarding how applications for admissions are likely to be judged. Ultimately, contextual admission policies have the potential to increase diversity among the admitted students at selective HEIs.